Epothilone B Facilitates Peripheral Nerve Regeneration by Promoting Autophagy and Migration in Schwann Cells - Zhou, Jianhua; Li, Shengyou; Gao, Jianbo; Hu, Yawei; Chen, Shaochu; Luo, Xinle; Zhang, Hao; Luo, Zhuojing; Huang, Jinghui (Frontiers in Cellular Neuroscience, 2020)
The search for drugs that can facilitate axonal regeneration and elongation following peripheral nerve injury has been an area of increasing interest in recent years. Epothilone B (EpoB) is an FDA-approved antineoplastic agent, which shows the capacity to induce α-tubulin polymerization and to improve the stability of microtubules. Recently, it has been increasingly recognized that EpoB has a regenerative effect in the central nervous system. However, the information currently available regarding the potential therapeutic effect of EpoB on peripheral nerve regeneration is limited. Here, we used a rat sciatic crush injury model system to determine that EpoB strikingly improved axonal regeneration and recovery of function. Also, EpoB (1 nM) did not result in significant apoptosis in Schwann cells (SCs) and showed little effect on their viability either. Interestingly, EpoB (1 nM) significantly enhanced migration in SCs, which was inhibited by autophagy inhibitors 3-methyladenine (3-MA). Since PI3K/Akt signaling has been implicated in regulating autophagy, we further examined the involvement of PI3K/Akt in the process of EpoB-induced SC migration. We found that EpoB (1 nM) significantly inhibited phosphorylation of PI3K and Akt in SCs. Further studies showed that both EpoB-enhanced migration and autophagy were increased/inhibited by inhibition/activation of PI3K/Akt signaling with LY294002 or IGF-1. In conclusion, EpoB can promote axonal regeneration following peripheral nerve injury by enhancing the migration of SCs, with this activity being controlled by PI3K/Akt signaling-mediated autophagy in SCs. This underscores the potential therapeutic value of EpoB in enhancing regeneration and functional recovery in cases of peripheral nerve injury.